Heterologous Expression and Functional Analysis of Exiguobacterium Algin Lyase Gene by Pichia pastoris - Hanwen Wu; Kai Hou; Yutong Jiang; Mingjian Luan; Yuxia Sun; Xi He; Xiangzhong Zhao (Fermentation)
Algin is the most abundant substance in alga. Alginate lyase degrades algin and produces algin monosaccharides, disaccharides, and oligosaccharides, which are widely used in bioenergy, food, medicine, and other fields. In this study, one Exiguobacterium strain isolated from rotten kelp exhibited a robust ability to degrade the alga. The sequencing of this strain revealed the presence of three different types of algin alginate lyase. Nevertheless, the expression of three genes in Escherichia coli revealed a lower alginate lyase activity compared to that of the original strain. After codon optimization, the gene with the highest activity of the three was successfully expressed in Pichia pastoris to produce recombinant EbAlg664. The activity of the recombinant enzyme in 5 L high-density fermentation reached 1306 U/mg protein, 3.9 times that of the original Exiguobacterium strain. The results of the enzymatic analysis revealed that the optimal temperature and the pH range of recombinant EbAlg664 were narrower compared to the original strain. Additionally, the presence of Cu2+ and Co2+ enhanced the enzymatic activity, whereas Mg2+ and Fe3+ exhibited inhibitory effects on the recombinant alginate lyase. The study offers a theoretical and practical foundation for the industrial-scale production of engineered Pichia pastoris with high alginate lyase activity.